Pengaruh Family Control, Environmental Management Accounting, dan Profitabilitas Terhadap Nilai Perusahaan - Dalila, Farah; Khairunnisa, Khairunnisa (Owner : Riset dan Jurnal Akuntansi, 2024)
In the last quarter of 2020, the capital market conditions cannot be impressive either. Many stocks have high liquidity and good prospects but have experienced a correction of -24.67% caused by the COVID-19 pandemic. A view of investors in seeing whether managers are successful in managing the resources owned by the company, which is usually associated with stock prices, is called the company's value. This study's purpose is to determine of family control, environmental management accounting, and profitability on firm value. The objects used in this study are LQ45 index companies listed on the Indonesia Stock Exchange. Based on several criteria in determining the sample, 17 company samples, or 85 data points. Analysis of research data using regression panel data using Eviews 12. The results indicate that family control, environmental management accounting, and profitability have a simultaneous effect on firm value. Meanwhile, family control and environmental management accounting do not have a positive effect on firm value, while the profitability variable has a significant positive effect on firm value.